Inhibiting anti-angiogenic VEGF165b activates a miR-17-20a-Calcipressin-3 pathway that revascularizes ischemic muscle in peripheral artery disease - Sonia Batan; Sivaraman Kuppuswamy; Madison Wood; Meghana Reddy; Brian Annex; Vijay Ganta (Communications Medicine, 2024)
Abstract Background VEGF165a increases the expression of the microRNA-17-92 cluster, promoting developmental, retinal, and tumor angiogenesis. We have previously shown that VEGF165b, an alternatively spliced anti-angiogenic VEGF-A isoform, inhibits the VEGFR-STAT3 pathway in ischemic endothelial cells (ECs) to decrease their angiogenic capacity. In ischemic macrophages (Møs), VEGF165b inhibits VEGFR1 to induce S100A8/A9 expression, which drives M1-like polarization. Our current study aims to determine whether VEGF165b inhibition promotes perfusion recovery by regulating the microRNA(miR)-17-92 cluster in preclinical PAD. Methods Femoral artery ligation and resection was used as a preclinical PAD model. Hypoxia serum starvation (HSS) was used as an in vitro PAD model. VEGF165b was inhibited/neutralized by an isoform-specific VEGF165b antibody. Results Here, we show that VEGF165b-inhibition induces the expression of miR-17-20a (within miR-17-92 (miR-17-18a-19a-19b-20a-92) cluster) in HSS-ECs and HSS-Møs vs. respective normal and/or isotype-matched IgG controls to enhance perfusion recovery. Consistent with the bioinformatics analysis that revealed RCAN3 as a common target of miR-17 and miR-20a, Argonaute-2 pull-down assays showed decreased miR-17-20a expression and higher RCAN3 expression in the RNA-induced silencing complex of HSS-ECs and HSS-Møs vs. respective controls. Inhibiting miR-17-20a induced RCAN3 levels to decrease ischemic angiogenesis and promoted M1-like polarization to impair perfusion recovery. Finally, using STAT3 inhibitors, S100A8/A9 silencers, and VEGFR1-deficient ECs and Møs, we show that VEGF165b-inhibition activates the miR-17-20a-RCAN3 pathway independent of VEGFR1-STAT3 or VEGFR1-S100A8/A9 in ischemic-ECs and ischemic-Møs respectively. Conclusions Our data revealed a hereunto unrecognized therapeutic ‘miR-17-20a-RCAN3’ pathway in the ischemic vasculature that is VEGFR1-STAT3/S100A8/A9 independent and is activated only upon VEGF165b-inhibition in PAD.